2020
DOI: 10.1002/ange.202007451
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation of WO3−x Dots with Remarkably Low Toxicity and Uncompromised Activity as Co‐reactants for Clinical Diagnosis by Electrochemiluminescence

Abstract: The exceptional nature of WO3−x dots has inspired widespread interest, but it is still a significant challenge to synthesize high‐quality WO3−x dots without using unstable reactants, expensive equipment, and complex synthetic processes. Herein, the synthesis of ligand‐free WO3−x dots is reported that are highly dispersible and rich in oxygen vacancies by a simple but straightforward exfoliation of bulk WS2 and a mild follow‐up chemical conversion. Surprisingly, the WO3−x dots emerged as co‐reactants for the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…In the sample, two main peaks were observed to be generated by W 6+ at 36.48 eV (W 4f7/2) and 38.57 eV (W 4f5/2), respectively, 37,38 while W 5+ showed two weak peaks at 35.38 eV (W 4f7/2) and 37.37 eV (W 4f5/2). 39,40 It reflects the oxidation state of different W species in the sample. In addition, as shown in the O 1s nuclear-level XPS spectrum (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the sample, two main peaks were observed to be generated by W 6+ at 36.48 eV (W 4f7/2) and 38.57 eV (W 4f5/2), respectively, 37,38 while W 5+ showed two weak peaks at 35.38 eV (W 4f7/2) and 37.37 eV (W 4f5/2). 39,40 It reflects the oxidation state of different W species in the sample. In addition, as shown in the O 1s nuclear-level XPS spectrum (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The supporting electrolyte was 0.1 M PBS (pH=7.5) with 0.1 M K2S2O8. According to the previously reported work, 2,32,[38][39] the ECL efficiency (ΦECL, %)…”
Section: Synthesis Of Pncds and Ncdsmentioning
confidence: 99%
“…Electrochemiluminescence (ECL) is a light-emitting process excited through electrochemical reactions, showing remarkable merits of high sensitivity, low background, quick response, ease of operation, and low cost of equipment. [1][2][3][4][5][6][7] Recently, multicolor ECL has attracted considerable attention for ECL-based biomedical applications ranging from multiplex bioassay to bioimaging, raising an increasing demand for exploiting luminophores with tunable emission wavelength. [8][9][10][11][12][13][14] Along this line, several pioneer works have been reported that multicolor ECL could be realized by combining or modifying ruthenium (II) and iridium (III) complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Smartly combining electrochemistry and chemiluminescence, electrochemiluminescence (ECL) or electrogenerated chemiluminescence, is a light emission process that occurs from the electron transfer between highly active radical species that are electrochemically generated [1][2][3]. ECL has become an essential modern electroanalytical technique with wide applications in the fields of biosensing [4][5][6], bioimaging [7][8][9], and immunoassays [10][11][12]. Furthermore, ECL investigation can also provide guidelines for light-emitting electrochemical cells (LECs) who has similar luminescent mechanisms.…”
Section: Introductionmentioning
confidence: 99%